Roadside Market, Trinidad, B.W.I. -25568 - (:unkn) unknown (My University, 2009)
Female vendors packing or unpacking their vegetables. The East Indian women are wearing white, tea-length dresses and odhni (fine veils). They appear to be barefooted.
Colour: Black and white; Style: Landscape; Other: Bordered, Divided
Keywords: Postcards; Trinidad and Tobago; Women merchants--Trinidad and Tobago; Markets--Trinidad and Tobago; Street vendors--Trinidad and Tobago; Women, Black--Trinidad and Tobago; Women, East Indian--Trinidad and Tobago; East Indians--Trinidad and Tobago; Vending stands--Trinidad and Tobago; Vegetables--Trinidad and Tobago; Stools--Trinidad and Tobago; Seating (Furniture)--Trinidad and Tobago; Baskets--Trinidad and Tobago; Bags; Women--Trinidad and Tobago; Architecture--Details; Wooden doors--Trinidad and Tobago; Clothing and dress--Trinidad and Tobago; Dresses--Trinidad and Tobago; Hats--Trinidad and Tobago; Veils--Trinidad and Tobago; Jewelry--Trinidad and Tobago; Bracelets--Trinidad and Tobago; Ethnic costume--India; Tables--Trinidad and Tobago; [1930]; Women's clothing--Trinidad and Tobago